2019
DOI: 10.3389/fpls.2018.01979
|View full text |Cite
|
Sign up to set email alerts
|

GmWRKY16 Enhances Drought and Salt Tolerance Through an ABA-Mediated Pathway in Arabidopsis thaliana

Abstract: The WRKY transcription factors (TFs) are one of the largest families of TFs in plants and play multiple roles in plant development and stress response. In the present study, GmWRKY16 encoding a WRKY transcription factor in soybean was functionally characterized in Arabidopsis. GmWRKY16 is a nuclear protein that contains a highly conserved WRKY domain and a C2H2 zinc-finger structure, and has the characteristics of transcriptional activation ability, presenting a constitutive expression pattern with relative ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 109 publications
3
88
0
Order By: Relevance
“…Similarly, OsHSFA3-overexpressing plants maintained higher biomass as compared to WT under drought stress, which further revealed its role in drought tolerance. These observations were in line with previous findings which revealed higher plant biomass and survival ability in drought-tolerant plants [40,52,53]. These findings indicate that OsHSFA3 induces drought tolerance in transgenic plants by different plant adaptations such as longer root length, reduced water loss and modulating the ABA level to protect from dehydration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, OsHSFA3-overexpressing plants maintained higher biomass as compared to WT under drought stress, which further revealed its role in drought tolerance. These observations were in line with previous findings which revealed higher plant biomass and survival ability in drought-tolerant plants [40,52,53]. These findings indicate that OsHSFA3 induces drought tolerance in transgenic plants by different plant adaptations such as longer root length, reduced water loss and modulating the ABA level to protect from dehydration.…”
Section: Discussionsupporting
confidence: 92%
“…ABA is an important plant stress signaling hormone which plays important role in drought stress tolerance via regulating expression of various stress-responsive genes [31,39,40]. Thus, we measured endogenous ABA levels in OsHSFA3-overexpressing lines and WT plants.…”
Section: Overexpression Of Oshsfa3 Increases Drought Tolerance By Decmentioning
confidence: 99%
“…, 2018; Ma et al . , 2019). Over the past 2 decades, studies have elucidated the importance of NF‐Ys in plant growth and stress responses, however the physiological and molecular mechanisms of action remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4, under drought condition, expression levels of all these genes were significantly higher in the transgenic lines compared with those in WT by 30% (HSP70B) to nearly 50% (RD29A and LEA14). Studies have reported rapid induction of the stress marker gene RD29A under various abiotic stresses, such as water deficit, and particularly in stress-tolerant plants, thus emphasized its role as indicator for resistance toward drought [71,73,74]. Herein, in correlation with higher resistance to drought of transgenic plants (Figure 2), RD29A expression was also found to be remarkedly induced, suggesting RD29A is one of GmRR34 target for mediating drought responses, through a direct and/or indirect manner.…”
Section: Discussionmentioning
confidence: 87%
“…Three well-known stress-responsive genes, RD29A, LEA14, and HSP70B, were also selected to examine their expression in our study to gain insights to the molecular function basis of GmRR34. Expression patterns of these genes have been considered important indicators for drought-responsive studies [71,72]. As shown in Figure 4, under drought condition, expression levels of all these genes were significantly higher in the transgenic lines compared with those in WT by 30% (HSP70B) to nearly 50% (RD29A and LEA14).…”
Section: Discussionmentioning
confidence: 99%